Recent progress of the ARegPKD registry study on autosomal recessive polycystic kidney disease - Ebner, Kathrin; Schaefer, Franz (Frontiers in Pediatrics, 2017)
Autosomal recessive polycystic kidney disease (ARPKD) is a rare monogenic disease with a severe phenotype often presenting prenatally or in early childhood. With its obligate renal and hepatic involvement, ARPKD is one of the most important indications for liver and/or kidney transplantation in childhood. Marked phenotypic variability is observed, the genetic basis of which is largely unknown. Treatment is symptomatic and largely empiric as evidence-based guidelines are lacking. Therapeutic initiatives for ARPKD face the problem of highly variable cohorts and lack of clinical or biochemical risk markers without clear-cut clinical end points. ARegPKD is an international, multicenter, retro- and prospective, observational study to deeply phenotype patients with the clinical diagnosis of ARPKD. Initiated in 2013 as a web-based registry (www.aregpkd.org), ARegPKD enrols patients across large parts of Europe and neighbouring countries. By August 2016 more than 330 patients from 16 mostly European countries have been registered in the ARPKD registry study with significant follow-up data. Thanks to comprehensive retro- and prospective data collection and associated biobanking, ARegPKD will generate a unique ARPKD cohort with detailed longitudinal clinical characterization providing a basis for future clinical trials as well as translational research. Hence, ARegPKD is hoped to contribute to the pathophysiological understanding of the disease and to the improvement of clinical management.
Gesehen am 15.11.2018